Why AI is Essential for the Future of Islamic Education: A Call for Ethical and Effective Implementation - M. Sukron Djazilan; Afib Rulyansah; Jauharotur Rihlah (LP. Ma'arif Janggan Magetan, 2024)
The integration of Artificial Intelligence (AI) in Islamic-based elementary schools presents both opportunities and challenges in balancing hard skills and soft skills while preserving Islamic educational values. This qualitative case study explores how AI supports religious education, ethical development, and STEM learning in two Islamic schools in Gresik, East Java. Using semi-structured interviews, classroom observations, and document analysis, the study examines the impact of AI on teacher-student interactions, personalized learning, and character formation. The findings indicate that AI enhances Quranic learning, ethical discussions, and academic proficiency by providing adaptive feedback, interactive learning tools, and automated assessments. However, while AI improves hard skills development, it requires additional pedagogical strategies to cultivate soft skills such as ethical reasoning, leadership, and communication. Educators emphasized that AI must complement rather than replace traditional teacher-led instruction to maintain the spiritual and moral aspects of Islamic education. Despite its benefits, AI implementation in Islamic schools faces several challenges, including technological infrastructure limitations, teacher readiness, and ethical concerns related to AI alignment with Islamic principles. The study highlights the importance of contextual AI customization, comprehensive teacher training, and ethical AI governance to ensure effective and culturally appropriate AI adoption. This study contributes to the growing discourse on AI in religious education and offers policy recommendations for integrating AI into Islamic curricula while maintaining the integrity of faith-based education. Future research should explore long-term impacts of AI on moral education, cross-cultural AI adoption, and strategies for ethical AI governance in faith-based learning environments.